Development of Integrated Thematic Learning Modules of Islamic Values for Grade VI Students at Elementary Madrasahs - Dewi, Ramla; Thaha, Hisban; Hutami, Eka Poppi; Maeduereh, Mustafakama (State Islamic Institute of Palopo, 2024)
This study aims to develop a thematic learning module integrated with Islamic values on the sub-theme